Crystallization and X‐ray diffraction analysis of a putative bacterial class I labdane‐related diterpene synthase. Issue 9 (1st September 2015) - Serrano‐Posada, Hugo; Centeno‐Leija, Sara; Rojas‐Trejo, Sonia; Stojanoff, Vivian; Rodríguez‐Sanoja, Romina; Rudiño‐Piñera, Enrique; Sánchez, Sergio
<x xml:space="preserve">Abstract</x> Labdane‐related diterpenoids are natural products with potential pharmaceutical applications that are rarely found in bacteria. Here, a putative class I labdane‐related diterpene synthase (LrdC) identified by genome mining in a streptomycete was successfully crystallized using the microbatch method. Crystals of the LrdC enzyme were obtained in a holo form with its natural cofactor Mg2+ (LrdC‐Mg2+) and in complex with inorganic pyrophosphate (PPi) (LrdC‐Mg2+–PPi). Crystals of native LrdC‐Mg2+ diffracted to 2.50 Å resolution and belonged to the trigonal space group P3221, with unit‐cell parameters a = b = 107.1, c = 89.2 Å. Crystals of the LrdC‐Mg2+–PPi complex grown in the same conditions as the native enzyme with PEG 8000 diffracted to 2.36 Å resolution and also belonged to the trigonal space group P3221. Crystals of the LrdC‐Mg2+–PPi complex grown in a second crystallization condition with PEG 3350 diffracted to 2.57 Å resolution and belonged to the monoclinic space group P21, with unit‐cell parameters a = 49.9, b = 104.1, c = 66.5 Å, β = 111.4°. The structure was determined by the single‐wavelength anomalous dispersion (SAD) technique using the osmium signal from a potassium hexachloroosmate (IV) derivative.